2009
DOI: 10.1590/s0037-86822009000600024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da doença de Chagas em gestantes da região sul do Rio Grande do Sul

Abstract: RESUMOAnticorpos antiTrypanosoma cruzi no cordão umbilical de 351 parturientes da Cidade de Pelotas, RS foram pesquisados a fim de investigar a prevalência da doença de Chagas em gestantes. Um (0,3%) caso foi identificado, não sendo detectada transmissão congênita. Salienta-se a importância da investigação da doença de Chagas em gestantes de zonas endêmicas ou provenientes destas.Palavras-chaves: Doença de Chagas. Cordão umbilical. Trypanosoma cruzi. Gestantes. ABSTRACTAnti-Trypanosoma cruzi antibodies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(6 reference statements)
0
7
1
Order By: Relevance
“…The remainder (n=27) made the diagnosis with other or mixed methods, including one or a combination of direct microscopy, serology, PCR, hemoculture, and xenodiagnoses. Sample sizes varied greatly from 1 30,31 to 4377 infants, 32 while the number of diagnosed congenital cases ranged from 0 (n=13 studies) to 267 infants. 32 After excluding the studies without congenital infections, the congenital transmission rates ranged from 0.75% 33 to 28.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The remainder (n=27) made the diagnosis with other or mixed methods, including one or a combination of direct microscopy, serology, PCR, hemoculture, and xenodiagnoses. Sample sizes varied greatly from 1 30,31 to 4377 infants, 32 while the number of diagnosed congenital cases ranged from 0 (n=13 studies) to 267 infants. 32 After excluding the studies without congenital infections, the congenital transmission rates ranged from 0.75% 33 to 28.6%.…”
Section: Resultsmentioning
confidence: 99%
“…This prevalence is lower than that reported in disease-endemic regions of Argentina and Bolivia, but higher than those reported in Peru and Brazil. [7][8][9] The most relevant T. cruzi infection risk-associated factors were age, knowledge of vector, rural residency and level of education. Similarly, Hidron and others using a multivariate model reported that longer residence in a disease-endemic province, residence in a rural area, and poor housing conditions were associated with T. cruzi infection.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Bolivia it varies from 20% to 60% and in Argentina, Brazil, Chile, Peru, and Paraguay it ranges from 0% to 40%. [7][8][9] Likewise, the probability of congenital transmission varies among countries because it is dependent on follow-up time for newborns and diagnostic techniques used, which usually differ from one study to another. [10][11][12] In Colombia, there are approximately 436,000 infected persons, nearly 5 million persons live in areas at risk for vector-borne domestic transmission, Chagas disease affects closely 130,000 women of childbearing age, and consequently, near 1,000 children with congenital Chagas disease are born annually.…”
Section: Introductionmentioning
confidence: 99%
“…Araujo et al [26] conducted an epidemiological study of CD involving pregnant women from the Brazilian town of Pelotas (Rio Grande do Sul state). A total of 351 umbilical cord serum samples obtained from the parturients were analyzed and only one case was positive.…”
Section: Reviewmentioning
confidence: 99%